Implementation of Corporate Social Responsibility (CSR) as an Embodiment of Corporate Environmental Social Responsibility in the Era of Globalization - Gandhi Pharmacista (Jurnal Info Sains : Informatika dan Sains, 2023)
Corporate Social Responsibility is a form of company contribution and responsibility towards the surrounding environment and aims at sustainable development by managing all its stakeholders. This research aims to determine and analyze the legal aspects of companies in providing Corporate Social Responsibility to the surrounding environment. Meanwhile, the research method used is qualitative, where the qualitative method aims to obtain a complete picture of a matter according to the views of the people being studied, and the results of this research explain that business operations are committed not only to increasing the company's financial profits, but also to socio-economic development. the region in a holistic, institutional and sustainable manner. With the provisions on the obligation to carry out CSR for companies in Indonesia, companies are not only expected to have Single Bottom Line responsibilities, namely responsibility for the company's financial condition only, but companies are also faced with Triple Bottom Line responsibilities. Therefore, companies that want to achieve corporate sustainability in creating CSR programs must not only pay attention to economic and social aspects, but also pay attention to environmental aspects so that the company's existence will be maintained and at the same time environmental sustainability. This means that CSR programs need to be aligned with the principles of sustainable development as mandated by the green constitution of the 1945 Constitution.